Solvency determinants of family takaful companies in Malaysia - Zein, Syaza; Abduh, Muhamad (2014)
The ability to understand and identify factors affecting solvency of family takaful company is crucial to various stakeholders of an insurance industry. The purpose of this study is to empirically study firm-specific and economic factors affecting solvency of family takaful companies in an emerging economy and well-regulated financial industry of Malaysia. Solvency is proxies by equity-to-asset and equity-to-technical reserve ratio. The investigation is done from year 2008 until 2012 on six family takaful companies using balanced panel data regression model. The study finds takaful leverage and contribution growth are statistically significant and positively related to solvency. Meanwhile, expenses and company size are factors that are statistically significant and negatively related to solvency. All these factors influencing solvency of family takaful companies shall be taken into account by various stakeholders in analysing the sustainability and performance of insurance industry in Malaysia dual financial system